Motives and barriers to physical activity participation among women civil servant of the supporting group in Putrajaya / Roayaah Zambri - Zambri, Roayaah (2016)
Physical activity has been proven to have a significant impact on individuals’ physical, psychological, physiological and social life. Despite all of these advantages, physical activity remains to be narrowed and dropped out from time to time. This scenario has been mostly occurred among women who are found to lead sedentary lifestyles compared to men. The necessity .to identify their motives and barriers to participating in physical activity is crucial since little is known about physical activity pattern particularly into demographic profiles, motives, barriers and physical activity levels among women civil servant in Malaysia. Hence, this study was conducted to examine the differences and the relationships on motives, as well as barriers to physical activity participation across physical activity levels. A total of 447 women civil servant completed a set of questionnaire on physical activity levels, motives and barriers to physical activity participation. The results found that 68% (N=143) of the women civil servants were classified into pre-contemplation, contemplation, and preparation stages which indicate they were not being physically active enough. Fitness and health, and appearance motives were found to be the most important motives, while personal well-being and cultures and religiosity were became the most barriers for them to participate in physical activity. The results showed that the motives among these women civil servants were significantly different (f (2, 438) = 2.12, p =.003; Wilks’ Lambda = .91) and were significantly correlated (r = .20, n =447, p < .01) with their physical activity levels. In addition, the results have showed that the barriers to physical activity participation and physical activity levels were also significantly different ( f (4, 436) = 4.86, p =.00; Wilks’ Lambda = .74) and correlated (r = .41, n =447, p < .01) It can be concluded that women in different level perceived different motives and barriers in order to participate in physical activity, while motives and barriers does influence and initiate the movement of physical activity levels among these women from non-active to active women. Therefore, any physical activity intervention attempts should emphasized more on the motives, while reducing barriers in order to enhance these women to be physically active. The findings also recommended an investigation on extensive sample on multiple setting as a future research.